Authenticity and Institutional Context: Individual Preferences in China. Issue 5 (20th October 2019) - Carroll, Glenn R.; Feng, Mi; He, Yuanqiong; O'Connor, Kieran; Wang, Lihua
Abstract: This study explores how and when the institutionalized classification system for products (or services) in a specific national market domain affects consumer perceptions of authenticity. We argue that "type authenticity" presupposes a well-established and taken-for-granted classification system for a product or service. In domains with such systems, individuals will place greater value on products or markets that exhibit high type authenticity—other forms of authenticity, including craft, moral, or idiosyncratic authenticity, will be less salient. By contrast, in domains without institutionalized systems, individuals will prioritize craft or moral or idiosyncratic authenticity over type authenticity. To test these arguments, we conducted studies in China where we asked participants to express preferences and make choices about products described to evoke various kinds of authenticity. We also asked these individuals to assess the authenticity of the producer organizations as well as their willingness to pay for associated products. Specifically, we tested the arguments with data on the appeal of various fictitious producers of leather handbags and green tea among Chinese individuals. While the leather handbag is known in China, it is not highly institutionalized whereas white tea clearly is. The findings generally support the hypotheses.